Meningkatkan Hasil Belajar Ekonomi Materi Koperasi Melalui Permainan Edukatif Finding Treasure Dengan Model Pembelajaran Problem Based Learning - Trisnawati, Eva; Kurniawan, Riza Yonisa; Wahyuningtyas, Endar (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
Education is a learning activities to develop according to the times, such as freedom to learn which emphasizes 21st century learning. 21st century learning is inseparable from learning in literacy skills, knowledge analysis, and use the tecnology in the learning process. researchers combined learning models with technology to suit the student centered in this study. This research uses collaborative classroom action research with instruments on student learning outcomes from pre test and post test scores.The result of the analysis achievement of student learning outcome seen from the first cycle is 80,56% with an average value of 80,83 and the second cycle with a percentage of 97,22% with an average value of 86,87. From these results it can be seen that the application of a problem based learning using educational media of finding treasure games can improve student learning outcomes.